Entrenching Gender Inequality in the Niger Delta through the Niger Delta Development Commission’s Interventions - Akinyoade, Demola V. (Àgídìgbo: ABUAD Journal of the Humanities, 2015)
Interventions are meant to cause positive changes in the life of a people. Extant literature has however, shown that they can equally impact negatively. This study relies on this widely acclaimed position in assessing the interventions of the Niger Delta Development Commission (NDDC) on one of the possible areas of impacts-gender. Empirical works on the Commission have not investigated the nature, dynamics and implications of the NDDC interventions on gender. What is the institutional capacity of the NDDC for gender sensitivity? How did the interventions impact on gender dynamics in beneficiary communities? The study adopted qualitative research methods-grounded theory and case study designs. Primary and secondary data )"ere collected through key-informant and in-depth interviews, documents and observation. ATLAS.ti 7.0 was used for data analyses. Data collection and analyses were iterative. Odi Community in Bayelsa State of Nigeria was selected as the case study. The Gender-Based Analysis of Intervention Framework (GBAIF) was used to assess the impacts of the interventions on gender dynamics of Odi. Findings show that the articulated guiding principles of the Commission stipulate gender sensitivity in its intervention programming. However, the NDDC lacks institutional capacity for gender sensitivity. Thus the interventions are gender-blind because the Commission does not mainstream gender in its interventions. Consequently, they impacts negatively on gender relations by inadvertently entrenching traditional power disequilibrium and gender roles between females and males. This happens because the interventions fail to recognise and include women group in its community engagement meetings; allocate more financial resources to males through income from wages as labourers in construction projects; by not making provision for women’s needs in their training programmes, hence discouraging women participation; and by designing special programmes such as Home Management Business Skills that entrench women’s traditional reproduction activities.